BETWEEN TABLOIDIZATION AND TEASER ADS: an analysis of clickbaittitles - Bueno, Thaísa Cristina (2018)
The purpose of this article is to identify which writing strategies are adopted by cyber newspapers, traditional and web native ones, in the construction of clickbait titles. The research starts from the categorization proposed by the Facebook to discern what would be a clickbait title and intends to detect the guidelines of advertising narratives that would be guiding this writing and interfering in its genesis. We start from the hypothesis that clickbait is a teaser, an advertising resource used in campaigns and product launches that has migrated to the writing press, subverting its structure and, therefore, de-characterizing it as a journalistic title. The study also aims to understand the reasons that guaranties the existence of this model, despite the hard criticism that clickbait strategies receive from researchers, vehiclesand readers.To achieve these objectives, the literature review is based on the studies of authors who discuss the journalistic title, the teaser in advertising and the sensationalism.